2006
DOI: 10.1016/j.bbalip.2005.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Na+/H+ exchanger in membrane phosphatidylserine exposure during human platelet activation

Abstract: Platelet membrane phosphatidylserine (PS) exposure that regulates the production of thrombin represents an important link between platelet activation and the coagulation cascade. Here, we have evaluated the involvement of the Na + /H + exchanger (NHE) in this process in human platelets. PS exposure induced in human platelets by thrombin, TRAP, collagen or TRAP+ collagen was abolished in a Na + -free medium. Inhibition of the Na + /H + exchanger (NHE) by 5-(N-Ethyl-N-Isopropyl) Amiloride (EIPA) reduced signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Another study has suggested that Na ϩ loading via Na ϩ /H ϩ exchange is involved in the regulation of PS scrambling in activated platelets. 73 These results clearly indicate that cytosolic calcium ions levels are not a unique player leading to the collapse of the membrane asymmetry. Whether these mechanisms may have a role in modulating the release of MPs in vivo deserves further scrutiny.…”
Section: Calcium Channels Ions and Microparticle Formationmentioning
confidence: 55%
“…Another study has suggested that Na ϩ loading via Na ϩ /H ϩ exchange is involved in the regulation of PS scrambling in activated platelets. 73 These results clearly indicate that cytosolic calcium ions levels are not a unique player leading to the collapse of the membrane asymmetry. Whether these mechanisms may have a role in modulating the release of MPs in vivo deserves further scrutiny.…”
Section: Calcium Channels Ions and Microparticle Formationmentioning
confidence: 55%
“…Alternatively, activation of the Na ϩ /H ϩ exchanger could facilitate cytosolic alkalinization. Interestingly, multiple studies have suggested the involvement of Na ϩ /H ϩ exchanger activity in mediating procoagulant activity and, presumably, procoagulant platelet formation (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized, however, that a decreased [Na ϩ ] may have 2 major consequences: it reduces the catalytic efficiency of thrombin, 15 and it likely causes inhibition of the Na ϩ /H ϩ exchanger, which may be involved in PS exposure during platelet activation. 16 We therefore compared the procoagulant response induced by collagen plus thrombin in low [Na ϩ ] solutions (ie, HEPES/choline buffer and HEPES/KCl buffer) with the response evoked in high [Na ϩ ] solution (ie, HEPES buffer). In these initial experiments, the procoagulant response was determined by the number of annexin-binding platelets measured by flow cytometry.…”
Section: The Influence Of High Extracellular [K ؉ ] On the Generationmentioning
confidence: 99%